Contribuição genética e reprodutiva de piracanjuba (Brycon orbignyanus) submetidos aos sistemas de reprodução seminatural e extrusão - Castro, Pedro Luiz de (2015)
Building hydroelectric dams in the course of Brazilian rivers is constantly associated with the large reduction in native fish populations. This action in addition to changing the entire water dynamics, is also a physical barrier that hinders the reproduction of migratory fish, such as piracanjuba (Brycon orbignyanus), strongly impacted species which is currently on the list of fish that are in danger of extinction. To mitigate the damages, a series of public policies were implemented, requiring biological compensation for the use of inland waters for electricity production and restocking, restoring natural populations from the release of alevins, is the most commonly adopted practice. However, if not carefully performed, this practice represents genetic and reproductive risk to populations still present in rivers, given the common loss of genetic variability in the production of alevins in the fish farms. The purpose of this study was to evaluate the influence of extrusion or semi-natural reproductive systems in different breeding (a female to three males and two females to six males), on the genetic and reproductive variability of the obtained progeny. 360 larvae samples were taken (90 larvae for each treatment) as well as a fin fragment from the 24 breeders used, and the genetic variability analyzes performed by PCR (Polymerase Chain Reaction) with amplification of eight microsatellite heterologous primers. 30 alleles were identified ranging from three to four per locus, so that 75% of higher frequency in the parental alleles were also in the offspring, demonstrating the maintenance of allelic frequencies in all treatments. The rates of expected heterozygosity and Shannon found the maintenance of genetic variability, observing the increase of its values in all progenies in relation to their parents. On the other hand, the parental contribution analyzes showed better results for treatments of the reproductive system by extrusion, since apparent relations of reproductive dominance were observed among the males in the semi-natural system, thus the increased number of breeders in the system was responsible for the intensification of this behavior. Moreover, better fertilization, hatching and mortality rates of breeders were observed in the semi-natural system, result associated to injuries caused by abdominal massage in extrusion. Thus, a reduction in the male x female ratio is indicated in the production of piracanjuba alevins in semi-natural system in fish farms aimed at restocking, while in extrusion systems increasing this ratio favors a more homogeneous parental contribution, but it is conditioned to effective participation of all males which can be guaranteed by semen quality analysis.